The Sources of Academic Stress among Students of the School of Medical Management and Information - Fatemeh Khademian; Mohtaram Nematollahi; Fariba Farahmand (Kerman University of Medical Sciences, 2017)
Background & Objective: Studying at a university is one of the important stressful situations Previous studies have shown the adverse effects of stress on students physical and mental health The aim of the current study was to determine the sources of academic stress and its relation to demographic variables in students at the School of Medical Management and Information of Shiraz University of Medical Sciences Iran Methods: This crosssectional study was conducted on 95 students (65 women and 30 men) with a mean age of 219 ± 1830 years (age range: 1830) The subjects were selected using stratified random sampling method Data were gathered using the Academic Stress Questionnaire (ASQ) and analyzed using descriptive statistical methods independent ttest the Pearson correlation coefficient and ANOVA Results: The findings indicated that the domain of difficulty managing work family and university had the highest mean score (402 ± 231) and the domain of difficulty with interaction at the university had the lowest mean score (261 ± 184) A significant negative association was found between age and the domain of difficulty managing work family and university (r = 0026 P = 001) In addition the mean score of second year students was significantly higher in the domains of difficulty with academic performance in class (P = 003) and difficulty with academic performance outside the class (P = 004) compared to other domains The most common stressors were observed in the domain of difficulty managing work family and university This domain was more important among younger students Conclusion: It is recommended that more attention be paid to this important issue in student educational and counseling programs